MetaMed - Medical meta data extraction and manipulation tool used in the semantically interoperable research information system - Vcelak, Petr; Kratochvil, Michal; Kleckova, Jana; Rohan, Vladimir (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
The MetaMed is a tool for data and meta data extraction primarily from a heterogeneous medical data. It is a non-interactive command line open source application for processing a large amount of data. An extracted meta data is stored in the Resource Description Framework and is structured by OWL ontologies. It enables a semantic interoperability. Meta data as an index data prevents us to solve different file format and version of raw files again and again for a following research. It enables a better performance. Indexed data can be directly used in a user interface and querying for an appropriate raw data can be done. The MetaMed and the research information system is confirmed with research primarily focused on a cerebrovascular diseases.